The need for stewardship of lands exposed by deglaciation from climate change. (28th December 2021) - Zimmer, Anaïs; Beach, Timothy; Klein, Julia A.; Recharte Bullard, Jorge
Abstract: Alpine glaciers worldwide will lose most of their volume by the end of the 21st century, placing alpine ecosystems and human populations at risk. The new lands that emerge from retreating glaciers provide a host of challenges for ecological and human adaptation to climate change. In these novel proglacial landscapes, ecological succession and natural hazards interplay with local agriculture, hydroelectric production, mining activities, and tourism. Research has emphasized the importance of understanding adaptation around socio‐environmental systems, but regional and global management efforts that support local initiatives and connect novel proglacial landscapes to ecological, social, and cultural conservation opportunities are rare and nascent. The characteristics of these emerging lands reflect the nexus of alpine ecosystems with socio‐political histories. Often overlooked in glacial‐influenced systems are the interdependencies, feedbacks, and tradeoffs between these biophysical systems and local populations. There is no coordinated strategy to manage and anticipate these shifting dynamics, while affirming local practices and contexts. There is an opportunity to initiate a new conversation and co‐create a governance structure around these novel landscapes and develop a new framework suitable to the Anthropocene era. This article first synthesizes the rapid socio‐environmental changes that are occurring in proglacial landscapes. Second, we consider the need for integrating "bottom‐up" with "top‐down" approaches for the sustainable management of proglacial landscapes. Finally, we propose establishing a transdisciplinary initiative with policy‐related goals to further dialogues around the governance and sustainable management of proglacial landscapes. We call for increased cooperation between actors, sectors, and regions, favoring multiscale and integrated approaches. This article is categorized under: Climate, Ecology, and Conservation > Conservation Strategies Abstract : In proglacial landscapes news challenges and opportunities arise as new ice‐free territories emerge. The proposed High Mountain Call to Action for Landscapes and Livelihoods (HiCALL) is a proposal to further dialogues around the governance and sustainable management of proglacial landscapes.